Test of Basic and Integrated Science Process Skills (T-BISPS): How do Form Four Students in Kelantan Fare? - Mohamad, Mohd Al-Junaidi; Eng Tek Ong, Eng Tek (Asian Journal of Assessment in Teaching and Learning, 2013)
This study aims to gauge the acquisition level of science process skills (SPS) amongst Form 4 students, analysing the data by gender, school location, and two way interaction between gender and school location. Using a causal comparative design, the authors developed psychometrically-supported 60 multiple-choice-item Test of Basic and Integrated Science Process Skills (T-BISPS) was administered to 245 form four students from two rural and two urban schools in Kelantan. The findings indicated that the students achieved an acquisition level which fell short of the twothirds benchmark (i.e., 66.67%) for the overall SPS (56.06%), basic SPS (59.29%) and integrated SPS (52.11%), and also for each of the specific science process skills except for communicating (67.35%), classifying (68.73%), and predicting (68.98%) skills. The results from the two-way factorial ANOVA indicated that, while there was no two-way gender and school location interaction effect and main gender effect, only the main school location effect was statistically significant in which urban students markedly outperformed rural students in the overall SPS, basic SPS and integrated SPS. The findings are discussed in relation to other studies and also in terms of possible contributory causes.